A method for detecting rash and fever illness‐associated viruses using multiplex reverse transcription polymerase chain reaction. (August 2017) - Matsushima, Yuki; Shimizu, Tomomi; Doi, Ikuko; Mizukoshi, Fuminori; Nagasawa, Koo; Ryo, Akihide; Shimizu, Hideaki; Kobayashi, Masae; Funatogawa, Keiji; Nagata, Noriko; Ishikawa, Mariko; Komane, Ayako; et al.
ABSTRACT: In this study, a new multiplex RT‐PCR method for detecting various viral genes in patients with rash and fever illnesses (RFIs) was constructed. New primer sets were designed for detection of herpes simplex viruses 1 and 2 (HSV1 and 2), and Epstein–Barr virus (EBV). The newly designed and previously reported primer sets were used to detect 13 types of RFI‐associated viruses by multiplex RT‐PCR assay systems. Moreover, to eliminate non‐specific PCR products, a double‐stranded specific DNase was used to digest double‐stranded DNA derived from the templates in clinical specimens. RFI‐associated viruses were detected in 77.0% of the patients (97/126 cases) by the presented method, multiple viruses being identified in 27.8% of the described cases (35/126 cases). Detected viruses and clinical diagnoses were compatible in 32.5% of the patients (41/126 cases). Sensitivity limits for these viruses were estimated to be 10 1 –10 3 copies/assay. Furthermore, non‐specific PCR products were eliminated by a double‐stranded specific DNase with no influence on sensitivity. These results suggest that this method can detect various RFI‐associated viruses in clinical specimens with high sensitivity and specificity.